How Merchant Towns Shaped Parliaments: From the Norman Conquest of England to the Great Reform Act - Angelucci, Charles; Meraglia, Simone; Voigtländer, Nico (American Economic Review, 2022)
We study the emergence of urban self-governance in the late medieval period. We focus on England after the Norman Conquest of 1066, building a novel comprehensive dataset of 554 medieval towns. During the Commercial Revolution (twelfth to thirteenth centuries), many merchant towns obtained Farm Grants: the right of self-governed tax collection and law enforcement. Self-governance, in turn, was a stepping stone for parliamentary representation: Farm Grant towns were much more likely to be summoned directly to the medieval English Parliament than otherwise similar towns. We also show that self-governed towns strengthened the role of Parliament and shaped national institutions over the subsequent centuries. (JEL D02, D72, D73, K11, K34, N43, N93)